F(x)=x2-8x+17

Simple and best practice solution for F(x)=x2-8x+17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for F(x)=x2-8x+17 equation:



(F)=F2-8F+17
We move all terms to the left:
(F)-(F2-8F+17)=0
We add all the numbers together, and all the variables
-(+F^2-8F+17)+F=0
We get rid of parentheses
-F^2+8F+F-17=0
We add all the numbers together, and all the variables
-1F^2+9F-17=0
a = -1; b = 9; c = -17;
Δ = b2-4ac
Δ = 92-4·(-1)·(-17)
Δ = 13
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$F_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$F_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$F_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(9)-\sqrt{13}}{2*-1}=\frac{-9-\sqrt{13}}{-2} $
$F_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(9)+\sqrt{13}}{2*-1}=\frac{-9+\sqrt{13}}{-2} $

See similar equations:

| (x+9)^4−64(x+9)^2=0 | | 110-19x-4=180 | | 8(1-7v)=8+8v | | -2x-4(6x-11)=174 | | F(x)=x2-2x+26 | | 6n-5n-11=3(2n-12) | | (x+9)4−64(x+9)2=0 | | 6x-12=-18-3x+6 | | 40-4b=-4(b-10) | | 46=n-7/3+11 | | 4.9+x=-9 | | 9/54=1/n | | 9(x-3)=13 | | --4=2p+10 | | -4b+4=5b-14 | | -158=-7(x+8)-10x | | n/n+6=-14 | | -3x–57=27+4x | | 1/5x+8=17 | | 4p-2=-6+6p | | 16-10n-5=65 | | (2/3)x+1=(2/3)x-1 | | |4x-12|=16 | | 5x-6(4x-16)=248 | | 7(x-5)=13 | | 4x+17+8x-35=90 | | 3(x=5)=2(3x+12) | | F(x)=x2+-100 | | m+2=2m-6 | | 78x-10x=30+418 | | -5m-15-4m=8+6m | | -4-2x=-20 |

Equations solver categories